An integrated economic decision and simulation methodology for e-recruiting process redesign. (31st August 2005) - Lee, In
Given hyper-competition and rapid environmental changes, one of the most critical sources of competitive advantage is to recruit and retain talented workers. While most large-sized organisations have adopted e-recruiting as a new process of reaching a large pool of potential job seekers, many of them have failed to achieve the maximum benefits because they do not have the appropriate infrastructure and recruiting process in place. This paper presents an integrated economic decision and simulation methodology for e-recruiting process design. The methodology for e-recruiting process design consists of four phases: development of the economic recruiting decision model; design of recruiting process; construction of simulation model; performance evaluation. Our simulation study indicates that the integration of the economic decision model contributed to a significant improvement in both the average recruiting process time and total recruiting cost compared to the e-recruiting process redesigned without integrating the economic decision model.